Hispano-Hebrew strophic poetry - Haxen, Ulf (Nordisk judaistik, 1981)
The conquest of Spain by the Arabs, allegedly prompted by leaders of the Jewish population after the fall of the Visigothic regime, 711, opened up an era in Medieval European history which stands unmatched as far as cultural enlightenment is concerned. Philosophy, belles lettres and the natural sciences flourished in the academies established by the Arab savants in the main urban centres. In the wake of the cultural revolution, a new branch of scholarship came into being - Hebrew philology. From the midst of this syncretistic, Mozarabic, milieu a remarkable poetic genre emerged. The study of Mozarabic (from Arabic, musta’riba, to become Arabicized) poetry has proved as one of the most fertile and controversial fields of research for Semitist and Romanist scholars during the past decades.